Identification of candidate genes for leaf scorch in Populus deltoids by the whole genome resequencing analysis. Issue 1 (December 2018) - Zhuang, Weibing; Liu, Tianyu; Qu, Shenchun; Cai, Binhua; Qin, Yalong; Zhang, Fengjiao; Wang, Zhong
Abstract Leaf scorch exists as a common phenomenon in the development of plant, especially when plants encounter various adversities, which leads to great losses in agricultural production. Both Jinhong poplar (JHP) and Caihong poplar (CHP) (Populus deltoids ) are obtained from a bud sport on Zhonghong poplar. Compared with CHP, JHP always exhibits leaf scorch, poor growth, premature leaf discoloration, and even death. In this study, the candidate genes associated with leaf scorch between JHP and CHP were identified by the whole genome resequencing using Illumina HiSeqTM. There were 218, 880 polymorphic SNPs and 46, 933 indels between JHP and CHP, respectively. Among these, the candidate genes carrying non-synonymous SNPs in coding regions were classified into 6 groups. The expression pattern of these candidate genes was also explored in JHP and CHP among different sampling stages. Combined with the qRT-PCR analysis, the results showed that genes associated with transport of various nutritional elements, senescence and MYB transcription factor might play important roles during the process of leaf scorch inPopulus deltoids . Four genes belonging to these three groups carried more than three SNPs in their coding sequence, which might play important roles in leaf scorch. The above results provided candidate genes involved in leaf scorch inPopulus deltoids, and made us better understand the molecular regulation mechanism of leaf scorch inPopulus deltoids .